Isovolumic loading of the failing heart by intraventricular placement of a spring expander attenuates cardiac atrophy after heterotopic heart transplantation. Issue 3 (27th June 2018) - Pokorný, Martin; Mrázová, Iveta; Šochman, Jan; Melenovský, Vojtěch; Malý, Jiří; Pirk, Jan; Červenková, Lenka; Sadowski, Janusz; Čermák, Zdeněk; Volenec, Karel; Vacková, Šárka; Maxová, Hana; et al.
Abstract : Cardiac atrophy is the most common complication of prolonged application of the left ventricle (LV) assist device (LVAD) in patients with advanced heart failure (HF). Our aim was to evaluate the course of unloading-induced cardiac atrophy in rats with failing hearts, and to examine if increased isovolumic loading obtained by intraventricular implantation of an especially designed spring expander would attenuate this process. Heterotopic abdominal heart transplantation (HTx ) was used as a rat model of heart unloading. HF was induced by volume overload achieved by creation of the aorto-caval fistula (ACF). The degree of cardiac atrophy was assessed as the weight ratio of the heterotopically transplanted heart (HW) to the control heart. Isovolumic loading was increased by intraventricular implantation of a stainless steel three-branch spring expander. The course of cardiac atrophy was evaluated on days 7, 14, 21, and 28 after HTx . Seven days unloading by HTx in failing hearts sufficed to substantially decrease the HW (−59 ± 3%), the decrease progressed when measured on days 14, 21, and 28 after HTx . Implantation of the spring expander significantly reduced the decreases in whole HW at all the time points (−39 ± 3 compared with −59 ± 3, −52 ± 2 compared with −69 ± 3, −51 ± 2 compared with –71 ± 2, and −44 ± 2 compared with −71 ± 3%, respectively; P <0.05 in each case). We conclude that the enhanced isovolumic heart loading obtained by implantation of the spring expander attenuates the development of unloading-induced cardiac atrophy in the failing rat heart.